Leishmaniose visceral e áreas de vulnerabilidade à saúde em Belo Horizonte, 2001-2005. - Andreza Pain Marcelino (2007)
The specific objective of this study was to evaluate if within the period between 2001 and 2005, the Visceral Leishmaniasis, in humans and canines in Belo Horizonte was spatially distributed according to the health risk area classificated by the Health Vulnerability Index (IVS), a local social indicator formulated by Belo Horizonte's Epidemiology and Information Office. By using the database relative to the canine cases from 2001 to 2004 and the human cases from 2001 to 2005 of VL, there was an analysis of them, through geoprocessing techniques and spatial analyses of slums. In the research, 439 (91.45%) human cases of VL out of a total of 480 known cases within the period between 2001 and 2005 were used and 11,861 (44.87%) canine cases out of a total of 26,431 known between 2001 and 2004. It was observed a significant VL cluster in the human cases, and six clusters in the canine cases, in which five of them were secondary clusters. The distribution of the human and canine VL did not show a direct correlation with the social economic level of the population.